A Model of Patent Trolls - Jay Pil Choi; Heiko Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper develops a model of patent trolls to understand various litigation strategies employed by nonpracticing entities (NPE). We show that when a NPE faces multiple potential infringers who use related technologies, it can gain a credible threat to litigate even when it has no such credibility vis-à-vis any single potential infringer in isolation. This is due to an information externality generated by an early litigation outcome for subsequent litigation. Successful litigation creates an option value against future potential infringers through Bayesian updating. This renders a credible litigation threat against the initial defendant and allows the NPE to extract more rents. We discuss policy implications including the adoption of the British system of “loser-pays” fee shifting and the use of injunctive relief.
Keywords: D43; L13; O30; 330; patent portfolios; patent litigation; non-practicing entities; patent troll